Non-military Defense in Border Areas: A Case Study of the Indonesia-Malaysia Border in West Kalimantan - Sahrun Gultom; Irdam Ahmad; Anwar Arifin; Edi Suhardono; David Yacobus (Budapest International Research and Critics University, 2022)
This study aims to explore the various problems faced by stakeholders, especially decision makers, in overcoming the complexities at the border between Indonesia and Malaysia in West Kalimantan. We obtained the latest conditions from in-depth interviews with 12 informants who were directly related to decision making at the location. We also conducted a series of focus group discussions and roundtable discussions to sharpen the multidimensional problems faced. We found that the problems on the border of West Kalimantan cover the dimensions of ideology, politics, technology, public safety, socio-culture, and the most important and the underlying is the economy, while legislation is not included. This study also proposes a hierarchy of dimensions of threats faced in border areas, which may also be applied in a similar context. We conclude that in overcoming the problem of non-military threats, mutual awareness among decision makers, especially BNPP, which is the leading institution in border area management, must be prioritized.